Manganese pollution in ground water of Pleistocene aquifers in Ho Chi Minh City area - Kỳ, Nguyễn Việt; Vân, Lê Thị Tuyết (Vietnam Journal of Earth Sciences, 2013)
Currently, Manganese (Mn) pollution in groundwater in Ho Chi Minh City was detected and became an interested issue for many researchers. In a well which belongs to the water supply company in HCM city, Mn contents comparing to standards increase many times and fluctuate by seasons markedly, while in some other wells, the Mn contents are still relatively stable. The content of Mn, similar to that of As, has a close relationship to iron content in the water. The correlation coefficient between iron and manganese reached 0.99856, showing that they have a syngenetic relationship.From some results of data processing on the concentration of Mn2+ and Fetc, it is stated that: the content of Mn2+ cannot be derived from the surface waste seeping down because it is minimum in the shallowest aquifer qp2-3. The concentration of Mn2+ ions increases in tandem with the depth. Their origin in groundwater related to the origin and composition of sediments of aquifer and aquiclude. The infiltration mechanism of Mn into the water is not clear. The treatment of Mn in groundwater is proposed in the paper, but other cheap solutions in accordance with the conditions of the community still need to find.